THE EVOLUTION OF POSTCOMMUNIST STATE IN THE EUROPEAN UNION : SECURE FUTURE OR THE PITFALL OF DEVELOPMENT ? - Gudžinskas, Liutauras (Politologija, 2015)
In this article the main attention will be devoted for the state and its place in postcommunist society. The state is the main institutional ensemble in political arena that directs our both political and everyday life, yet it itself is usually resilient for any radical changes even if it largely does not suffice the expectations of its citizenry. The article consists of three chapters. Firstly, I will consider the phenomenon of transformation of postcommunist state, its internal logic and essential causes that determined clear divergence of developmental paths in the postcommunist space. I will argue that the main explaining factor of success of transitions of some postcommunist countries and of failure for other ones has been the degree of embeddeness of national identity and stateness in the society. In other two chapters the attention will be paid for the development of postcommunist states after their accession in to the EU and for evolution of different trajectories. European integration changes the very role of state and thus puts its own challenges worth of deeper evaluation. Five years since the EU enlargement to the East is not the sufficient period of time in order to make final conclusions about the changes of these countries. However, the current tendencies do not deny the concerns about possible complications of development of postcommunist countries at the circumstances of the European integration. Firstly it is evidenced by the instability of party systems that is ubiquitous in the whole region, the increase of popularity of populist movements, politicization of civil service and the reducing level of administrative capacities. For some of these countries (including Lithuania) the situation is aggravated by the “semi-peripheral” position in the international economy. The evidence shows that the divide between “semi-core” and “semi-peripheral” countries in Central and Eastern Europe has become quite stable and may have its implications for the future. One of the puzzles I will consider is the increasing political alienation and distrust of state in Lithuania despite the fact that in some important areas of development of state structures, according to the various evaluations it has been a frontrunner in the region. My answer to this puzzle mainly will deal with the peculiarities of the taken path of state development which is resilient to be changed (and European integration seemingly even further solidifies it), yet it mismatches with the role of state that is wanted in the society.